ASSESSMENT OF NORMAL LIVER PORTAL VEIN AND COMMON BILE DUCT USING DOPPLER ULTRASONOGRAPHY - Mustafa, Ashraf; Elfadi, Mohamad; Elnabi, Mohamed Gar; Ahmed, Mona; Sulieman, Abdelmoneim (International Journal of Research -GRANTHAALAYAH, 2018)
Ultrasound imaging plays a vital role in the evaluation of many tissue or organs disorder. The objective of this study was to evaluate normal liver portal vein (PV) and common bile duct (CBD) using Doppler Ultrasonography (Duplex). Two ultrasound machines equipped with linear and curvilinear probes used in this study (Toshiba and ALOKA, Japan) during the period from 1st April 2016 to 30th July 2017. A total of 300 (48% males; 52% females) healthy subjects were participated in this study with age range from 16-22 years old. The mean intrahepatic portal vein velocity is between (14.98±1.92) cm/s; and the diameter range is (9.76±2.09). In frequency distribution of the extrahepatic portal vein velocity values, the majority is in the range (14-15 cm/s) which is equal to the half of the examined subjects. The extra hepatic PV versus intra hepatic portal vein velocities was found to be more in normal liver, where the velocity increased by 0.31 cm/s inside the liver per each cm/s of the extrahepatic for the normal liver.